Consequences of Implementing Neutralizing Buffered Peptone Water in Commercial Poultry Processing on the Microbiota of Whole Bird Carcass Rinses and the Subsequent Microbiological Analyses - Wages, Jennifer A.; Dittoe, Dana K.; Feye, Kristina M.; Ricke, Steven C. (Frontiers in Microbiology, 2022)
In 2016, the United States Department of Agriculture (USDA) Food Safety and Inspection Service (FSIS) established guidelines which modified the Buffered Peptone Water (BPW) rinsate material to include additional compounds that would better neutralize residual processing aids and allow for better recovery of sublethal injured Salmonella spp. cells. While the added compounds improved the recovery of Salmonella spp., specific data to understand how the new rinse agent, neutralizing Buffered Peptone Water (nBPW), impacts the recovery of other microorganisms such as Campylobacter spp. and indicator microorganisms is lacking. Therefore, this study evaluated the impact of rinse solutions (BPW or nBPW) used in whole bird carcass rinsate (WBCR) collections on the subsequent microbiome and downstream culturing methodologies. Carcasses exiting a finishing chiller were rinsed in 400 mL of BPW or nBPW. Resulting rinsates were analyzed for Enterobacteriaceae (EB), Salmonella, and Campylobacter spp. prevalence and total aerobic bacteria (APC) and EB load. The 16S rDNA of the rinsates and the matrices collected from applied microbiological analyses were sequenced on an Illumina MiSeq®. Log10 transformed counts were analyzed in JMP 15 using ANOVA with means separated using Tukey’s HSD and prevalence data were analyzed using Pearson’s 2 (P ≤ 0.05). Diversity and microbiota compositions (ANCOM) were analyzed in QIIME2.2019.7 (P ≤ 0.05; Q ≤ 0.05). There was an effect of rinsate type on the APC load and Campylobacter spp. prevalence (P < 0.05), but not the quantity or prevalence of EB or Salmonella spp. prevalence. There were differences between the microbial diversity of the two rinsate types and downstream analyses (P < 0.05). Additionally, several taxa, including Streptococcus, Lactobacillus, Aeromonas, Acinetobacter, Clostridium, Enterococcaceae, Burkholderiaceae, and Staphylococcaceae, were differentially abundant in paired populations. Therefore, the rinse buffer used in a WBCR collection causes proportional shifts in the microbiota, which can lead to differences in results obtained from cultured microbial populations.